The Behavioral Finance of MSME: Digital Finance, Managerial Biases, Financial Literacy - Risman, Asep (Dinasti Publisher, 2024)
This research aims to find empirical evidence of influence digital finance, managerial biases, and financial literacy on the MSMEs financial behavior. The population of this research is all MSMEs in DKI Jakarta. The sample used in this research was 200 respondents (MSME owners) from all 210 MSMEs who were willing to become respondents. Sampling was carried out using random techniques. Data collection was carried out by manually and online distributing questionnaires using Google Forms, and measured using a 5-point Likert scale. Data processing was carried out using Partial Least Square (PLS) software. The results of this research show that digital finance and financial literacy positively affect the MSMEs financial behavior. However, managerial biases does not affect the MSMEs financial behavior.